Pengaruh DAU,DAK, dan DBH terhadap Kemandirian Daerah Kabupaten/Kota di Provinsi Jawa Barat - Josefan Dohardo Sihite; Winwin Yadiati (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the effect of balancing funds consisting of the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on regional financial independence in district and city governments in West Java Province by using quantitative methods taken based on 260 sample data sourced from financial data in local government financial reports. The hypothesis is tested using multiple regression using SPSS_25 software. The sampling method used is purposive sampling which is grouped into four quadrants based on the characteristics of Regional Original Revenue (PAD) and the amount of balancing fund acquisition. The hypothesis is tested using multiple regression using SPSS_25 software. The results show that the impact of DAU varies between quadrants where local governments with high PAD and low balancing fund revenue positively influence local financial independence. Then governments with high PAD and high balancing funds and local governments with low PAD and high balancing funds did not show a significant effect. Meanwhile, local governments with low PAD and low balancing funds negatively and significantly influence regional financial independence. DAK has a significant positive effect and is the most influential factor compared to DAU and DBH. On the other hand, the DBH provision does not significantly affect the financial independence of district and city governments in all quadrants.